Síndrome de Gabriela: resistência e aceitação de tecnologias de informação e comunicação em uma comunidade rural de João Pessoa - Brito, Raissa Carneiro de (2015)
This research aims to identify which are the reasons that lead people from rural communities to overcome the challenges of handling technological devices when acquire new habits on their routines. Evidences related to these difficulties which the subject experiences technology usage is called, in this research, by “Gabriela’s Syndrome”, term that started to be used commonly after the soap opera “Gabriela cravo e canela”, written by Jorge Amado, in which Gabriela was the protagonist. She was a simple woman who did not get used to the urban life. The soundtrack says “... I was born on this way. I am just like this way. I will be always like this way that is my own way, Gabriela…”. The project “Luz do Saber”, at the rural community in Engenho Velho, Joao Pessoa, is an opportunity for people who live there being able to be literate through interactive activities like didactics games on the computer that help the student to become literate. However, despite all these resources offered by the program, it was verified the a strong resistance by people due to the technology usage – aspect that means changing of habits and costums. The analysis of the phenomenon found at this community is helped by the theory of Digital Limitations that was developed by Bellini et al. (2010), which presents a tridimensional model of Access Limitation, Informational Cognitive Limitation and Behavioral Limitation. This research investigates what motivates these students to overcome their limitations and attend their project’s classes. It was conducted through the construction of theoretical references about the project’s subject and counted on Focal Group’s support of data collection technic, which it was discussed questions based on TAM’s model (model of acceptation technology) under analysis of public opinions contente. Referencing this procedure, it will be produced advices which other similar social projects can take in order to target their goals and a higher popular acceptance. As a result, it was proven that applications of cognitive theory and social learning in pedagogical methodologies help to overcome the resistence to the challenge of changing and the usage of ICTs (Information and Communication Technologies).